Alabama Bass Alter Reservoir Black Bass Species Assemblages When Introduced Outside Their Native Range. (6th March 2023) - Sammons, Steven M.; Dorsey, Lawrence G.; Loftis, C. Scott; Chrisman, Preston; Scott, Mark; Hammonds, John; Jolley, Michael; Hatcher, Hunter; Odenkirk, John; Damer, John; Lewis, Matthew R.; Peatman, Eric J.
Abstract: Black bass Micropterus spp. stocked outside of their native range have often been implicated in declines of native fishes, but impacts of these stockings on native congeners have been examined less commonly and almost never in reservoirs. Relative abundance and creel data were obtained from seven reservoirs (632–13, 156 ha) in four southeastern states where Alabama Bass M. henshalli had been illegally stocked. Genetics data for black bass were collected in nine more reservoirs in five southeastern states where similar introductions occurred. In each case, Alabama Bass introduction was swiftly followed by sweeping changes in the black bass composition. Largemouth Bass M. salmoides relative abundance declined by 42–77% after Alabama Bass introduction in four of five reservoirs, but total black bass relative abundance was unchanged in three of them, indicating that Alabama Bass essentially replaced Largemouth Bass. Alabama Bass or their hybrids dominated the black bass genetic sample in five of nine reservoirs, and pure specimens of non‐Alabama Bass species composed <50% of the sample in six of nine reservoirs. Smallmouth Bass M. dolomieu were virtually extirpated via hybridization with Alabama Bass in two of the study reservoirs, and genetically pure fish were rare in several others. These changes occurred over relatively short time intervals, often within 10 years after detection of Alabama Bass, stressing the need for continual vigilance via routine monitoring and a proactive public relations campaign to discourage and limit new introductions. The leading edge of the Alabama Bass invasion now encompasses several notable Smallmouth Bass fisheries in North Carolina and is on the border of numerous others in Tennessee, Virginia, and beyond. The spread of nonnative black bass, such as the Alabama Bass highlighted in this article, constitutes one of the greatest threats to conserving native black bass fisheries.